The Decline of Japanese International Students - Shimmi, Yukiko (International Higher Education, 2011)
The number of Japanese students who study in the United States has decreased recent years. Several structural issues that are influencing the current declines are explored: a demographic shift, an increased capacity at domestic universities, an economic stagnation, the season of job-hunting for Japanese college students, and academic requirements. Then, new trends and approaches for the increase are discussed.